Project management of investment portfolios of a company and its innovation development - Bohach, K. S; Dudnyk, A. V. (Dnipro University of Technology, 2025)
The paper presents the results of the US financial markets’ study from the perspective of attracting investment resources for the development of the Ukrainian economy. Special attention is paid to the possibilities of using project management methods in the implementation of innovative projects for the development of enterprises. У статті представлено результати дослідження фінансових ринків США з точки зору залучення інвестиційних ресурсів для розвитку економіки України. Особливу увагу приділено можливостям використання гнучких та класичних методів управління під часреалізації інноваційних проєктів розвитку підприємств.
Управління проєктами інвестиційних портфелів компанії та її інноваційного розвитку
Keywords: project management; investment management; management; digitalization; business project; capital; управління проєктами; проєктний менеджмент; управління інвестиціями; менеджмент; цифровізація; бізнес-проєкт; капітал.